3D scaffolding of fast photocurable polyurethane for soft tissue engineering by stereolithography: Influence of materials and geometry on growth of fibroblast cells. (5th October 2020) - Farzan, Afsoon; Borandeh, Sedigheh; Zanjanizadeh Ezazi, Nazanin; Lipponen, Sami; Santos, Hélder A.; Seppälä, Jukka
Graphical abstract: Highlights: Fast photocuring PUs were synthesized through solvent free method. Flexible PU elastomers showed good mechanical properties needed for soft tissue scaffold. 3D scaffold with high resolution and complex geometry was fabricated for soft tissue engineering using SLA. High biocompatibility on dermal fibroblast cells was obtained using PU/PCL/PEG. 3D printed scaffold showed higher cell attachment compared with casted film. Abstract: Tissue engineering can benefit from the availability of three-dimensional (3D) printing technologies that make it possible to produce scaffolds with complex geometry. Chemical, mechanical, and structural properties should be considered in scaffold design and development since these properties affect cell adhesion, proliferation, and differentiation. To this end, in this study, we developed a series of fast photocuring polyurethanes (PUs), using poly(ε-caprolactone) (PCL) and/or polyethylene glycol (PEG) as microdiols, using a solvent-free method and stereolithography strategy for the fabrication of elastic 3D-printed scaffold. The effects of different diols on the hydrolytic degradation, thermal and mechanical properties, and hydrophilicity of PUs were evaluated. The results showed that PEG-containing PUs had higher degradation rates, and the tensile strength of PU/PCL/PEG was 1.4 and 2 times higher than that of PU/PEG and PU/PCL, respectively. Moreover, the effect of different diols and scaffold geometry on toxicity and cell attachment were studied in vitro . The results of MTT and AlamarBlue assays on dermal fibroblast cells showed high proliferation of printed PU/PCL/PEG scaffold with no sign of cytotoxicity. In addition, compared to cast film PUs, relatively high cell attachment was seen on the surface of printed PU/PCL/PEG even after 4 days. Therefore, 3D printed PU/PCL/PEG showed high applicability in soft tissue engineering, especially for scaffold development.